Welfare Benefits and Working Conditions of Teachers in The Schools Division in Northern Mindanao, Philippines - Dadulo, Evangeline P.; Canencia, Oliva P. (JPAIR Multidisciplinary Research, 2010)
This study explored how effective is the implementation of the project for the teachers’ assistance for optimum well-being specific to welfare benefits and working conditions of teachers in Northern Mindanao, Philippines. This also identifies major problems/issues and concerns/gaps encountered by public school teachers in relation to the welfare benefits and working conditions of DepEd teachers in Northern Mindanao. A survey questionnaire was given to 210 teachers in Northern Mindanao (Region X) which comprised the provinces of Misamis Oriental, Bukidnon and Misamis Occidental. Descriptive statistics was employed in this study while inferential statistics was used in the analysis of selected variables. Findings revealed that welfare benefits extended to the DepEd teachers in Region 10 were: health care benefits, scholarships, trainings and seminars extended. In terms of housing benefits, generally only very few teachers availed of housing benefits specifically availed from PAGIBIG through housing loans and followed by GSIS housing loans. The rest of the teachers availed thru Home Mortgage Loan, Cooperative and FICCO. Only few teachers availed on the scholarship programs, especially the doctoral degree. This is so because only few scholarships were offered to teachers and in most cases, teachers obtained their master’s and doctoral degree using their own personal expense. As to the trainings and seminars attended by teachers, most of these were sponsored by DepEd specifically on Basic Education Curriculum.